2007
DOI: 10.1300/j367v04n02_04
|View full text |Cite
|
Sign up to set email alerts
|

The Experiencing, Negotiation, Breaking, and Remaking of Gender Rules and Regulations by Queer Youth

Abstract: Earlier research positioned queer students as victims, and more recent scholarship positions them as agents. This study works to recognize and learn from the multiple subject positions of these youth by documenting subtleties regarding the experiences and negotiations of gender rules and regulations. When youth claim multiple subject positions, they are better able to identify, name, and work against oppression. Educators need to strive to make schools spaces where all students can engage in story lines that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
(10 reference statements)
1
19
0
Order By: Relevance
“…Scholars have documented the ways schools are sites of gender and sexuality policing (Best ; Blackburn ; Epstein ; Epstein et al ; Ferguson ; Fetner et al ; Phoenix ; Renold ; Rofes ; Toomey et al ; Pascoe ), and one only has to look at the daily news of youths who are bullied because of gender or sexual nonconformity to see that schools are central to the lived experiences of marginalized youths and the construction of deviant masculinities. The current story of Lila Perry, a transgender teen in Missouri, provides a salient example of all of the ways that abandoning hegemonic performances of masculinity lead to social sanctions.…”
Section: Youth Masculinities: Media Schools and The Shortcomings Ofmentioning
confidence: 99%
“…Scholars have documented the ways schools are sites of gender and sexuality policing (Best ; Blackburn ; Epstein ; Epstein et al ; Ferguson ; Fetner et al ; Phoenix ; Renold ; Rofes ; Toomey et al ; Pascoe ), and one only has to look at the daily news of youths who are bullied because of gender or sexual nonconformity to see that schools are central to the lived experiences of marginalized youths and the construction of deviant masculinities. The current story of Lila Perry, a transgender teen in Missouri, provides a salient example of all of the ways that abandoning hegemonic performances of masculinity lead to social sanctions.…”
Section: Youth Masculinities: Media Schools and The Shortcomings Ofmentioning
confidence: 99%
“…However, his story equally suggests that this was an ongoing negotiation of power between his boss and himself. Joseph's story resonates with wider discussions of young LGBQ people's capacity to transcend victim identities and position themselves as resourceful and creative agents in speaking back to oppressive experiences (Blackburn, 2007;Hillier & Harrison, 2004). Simultaneously, there are also clear constraints within work relationships and work cultures on how far young employees can extend their power as autonomous agents.…”
Section: Downloaded By [Newcastle University] At 19:34 20 December 2014mentioning
confidence: 85%
“…Empirical research across a variety of fields has demonstrated that individuals whose bodies, gender expressions and/or sexual orientations place them outside the socially accepted range of heteronormative expectations negotiate increased risks of marginalization. The consequences of such risks may negatively impact their abilities to successfully perform in a variety of institutional contexts, such as leisure activities, education settings, and employment situations (Blackburn, 2007;Ezzell, 2009;Grossman, 1992;Robinson & Espelage, 2011).…”
Section: Unlinking Identitiesmentioning
confidence: 99%